(untitled) (Mustansiria Dental Journal, 2024)
This research evaluates the faciolingual inclination of people in Mosul city as a base bracket design for straight wire arch technique (SWA) 50 study models (25 females) used aged 12-15 years, they concomitant with six keys of normal 52 .that suggested by Andrews The data then subjected to statistical evaluation at p<0.05, description of the data (mean SD.. minimum, maximum) also the correlation of all the teeth and comparison for both sexes. )The result show a higher record in lower central and lateral incisors in males (17.0 whereas a lowest record found in lower iirst molar in males (-30.0). A high correlation can be seen among anterior teeth and among posterior teeth with each other